2017
DOI: 10.1038/s41598-017-04479-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tenofovir disoproxil fumarate in preventing vertical transmission of hepatitis B in pregnancies with high viral load

Abstract: This study was a meta-analysis of the literature on the efficacy and safety of tenofovir disoproxil fumarate (TDF) in preventing vertical transmission of hepatitis B in pregnancies with high viral load. Four observational studies and one randomized controlled trial involving 585 pregnant women and 595 newborns were included in the meta-analysis. TDF was more effective than the placebo in reducing vertical transmission in HBeAg-positive chronic hepatitis B (CHB) pregnancies with high serum HBV-DNA levels (OR = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 35 publications
2
26
0
3
Order By: Relevance
“…As far as the safety is concerned, the two treatments showed good tolerability in this study, which is in agreement with previous reports . For TDF, the most frequent adverse reaction was mild‐to‐moderate gastrointestinal symptoms at a frequency comparable to the published results, even discontinuation has been reported previously .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As far as the safety is concerned, the two treatments showed good tolerability in this study, which is in agreement with previous reports . For TDF, the most frequent adverse reaction was mild‐to‐moderate gastrointestinal symptoms at a frequency comparable to the published results, even discontinuation has been reported previously .…”
Section: Discussionsupporting
confidence: 92%
“…The efficacy and safety of LdT administration in preventing MTCT have been extensively studied in prospective and retrospective studies . Recommended as the first‐line antiviral medication by all the major guidelines of the liver diseases associations, efficacy and safety of TDF usage in CHB‐infected pregnant women have been confirmed by increasing evidence . In our previous study enrolling 48 CHB mothers with LAM‐resistant HBV stains, TDF also showed substantial efficacy in HBV DNA suppression and MTCT prevention.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Based on existing data for South Africa, screening and treating women with TDF from 28 weeks of pregnancy to four weeks post-delivery reduces the number of infants with HBV at six months. Previous studies have also reported on the safety and effectiveness of TDF for HBV PMTCT (13,28). There is evidence for the cost-effectiveness of combining antiviral therapy during pregnancy with HBV immunoprophylaxis, as highlighted by a systematic review and meta-analysis carried out in China (29) and a study conducted in North America (30).…”
Section: Discussionmentioning
confidence: 99%
“…The use of antivirals during pregnancy can therefore be included as an additional measure to decrease transmission risk (12). Tenofovir disoproxil fumarate (TDF) has a track record of safety and efficacy in this setting (13,14), and is included in some guidelines for HBV PMTCT (6,15).…”
Section: Introductionmentioning
confidence: 99%